Postman Flows: A Visual Programming Tool for Building API-Powered Apps and Workflows - Krosnick, Rebecca (Proceedings (IEEE Symposium on Visual Languages and Human-Centric Computing), 2024)
Flows is a new visual dataflow programming tool from Postman for creating API-powered applications and workflows. Users chain together nodes that make API calls, process and manipulate data, and present data visually. Flows enables API producers to demonstrate API use cases, builders to prototype API-powered apps quickly, and individuals with limited programming experience to actually create software. Thousands of developers, solution architects, QA engineers, and hobbyists use Flows every day to build and share new applications and workflows. To make building with Flows even easier, we are also exploring AI-powered approaches to create and edit flows with natural language.